Synthesis and electrical properties of lead-free piezoelectric Bi0.5Na0.5TiO3 thin films prepared by Sol-Gel method. Issue 4 (April 2018) - Dargham, S. Abou; Ponchel, F.; Abboud, N.; Soueidan, M.; Ferri, A.; Desfeux, R.; Assaad, J.; Remiens, D.; Zaouk, D.
Abstract: Lead-free Bi0.5 Na0.5 TiO3 (BNT) piezoelectric thin films were deposited on Pt/TiOx /SiO2 /Si substrates by Sol-Gel method. A dense and well crystallized thin film with a perovskite phase was obtained by annealing the film at 700 °C in a rapid thermal processing system. The relative dielectric constant and loss tangent at 12 kHz, of BNT thin film with 350 nm thickness, were 425 and 0.07, respectively. Ferroelectric hysteresis measurements indicated a remnant polarization value of 9 μC/cm 2 and a coercive field of 90 kV/cm. Piezoelectric measurements at the macroscopic level were also performed: a piezoelectric coefficient (d33effmax ) of 47 pm/V at E = 190 kV/cm was obtained. The piezoresponse force microscopy data confirmed that BNT thin films present ferroelectric and piezoelectric behavior at the nanoscale level.